2016
DOI: 10.1088/0268-1242/31/4/043002
|View full text |Cite
|
Sign up to set email alerts
|

Towards monolithic integration of germanium light sources on silicon chips

Abstract: Germanium (Ge) is a group-IV indirect band gap semiconductor, and therefore bulk Ge cannot emit light efficiently. However, the direct band gap energy is close to the indirect one, and significant engineering efforts are being made to convert Ge into an efficient gain material monolithically integrated on a Si chip. In this article, we will review the engineering challenges of developing Ge light sources fabricated using nano-fabrication technologies compatible with complementary metaloxide-semiconductor proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 208 publications
0
39
0
9
Order By: Relevance
“…Intrinsic bulk Ge is an indirect band-gap material, but it can be converted to a quasi-direct band gap material due to the small separation between the  and L valley (136 meV) [1]. It was shown that the direct band gap of Ge can be realized by tensile strain engineering, alloying with Sn or ultra-high n-type doping [2][3][4][5]. By using only one of these methods it is extremely difficult to achieve a direct band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic bulk Ge is an indirect band-gap material, but it can be converted to a quasi-direct band gap material due to the small separation between the  and L valley (136 meV) [1]. It was shown that the direct band gap of Ge can be realized by tensile strain engineering, alloying with Sn or ultra-high n-type doping [2][3][4][5]. By using only one of these methods it is extremely difficult to achieve a direct band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 2(n) and 2(o) respectively show the corresponding calculated Ge 2 3 Λ 1c (A 1 ) and 2 3 ∆ 1c (A 1 ) character of the Ge 53 C 1 K = 0 CB eigenstates. The Ge Γ 2 c , 2 3 Λ 1c (A 1 ) and 2 3 ∆ 1c (A 1 ) character of the CB edge eigenstate is highlighted in Figs. 2(m) -2(o) using green, red and blue coloring, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Второе направление имеет неоспоримое преимущество простоты интеграции создаваемых источников излучения с элементами кремниевой интегральной наноэлектроники, однако имеет и существенный недостаток, связанный с низкой эффективностью излучательной рекомбинации носителей заряда в гетероструктурах на основе непрямозонных материалов IV группы. Для повышения эффективности излучательной рекомбинации в этих материалах в литературе рассматривались различные стратегии (см., например, обзоры [1,2]), одной из которых является модификация зонной структуры Ge. Несмотря на то что Ge является непрямозонным полупроводником (абсолютный минимум зоны проводимости находится в точке L зоны Бриллюэна), при 300 K ширина прямой запре-щенной зоны (E dir g = 0.8 эВ) лишь на ∼ 140 мэВ больше, чем непрямой (E ind g = 0.66 эВ).…”
Section: Introductionunclassified